Penggunaan Kitab Prakom Untuk Meningkatkan Kemampuan Minat Membaca Kitab Kuning Di Pondok Pesantren MIftahul Ulum Yosorati Sumbeberu Jember - Abdus Salam; Moh Sahlan (4, 2026)
This study aims to describe and analyze the use of the Prakom Book to improve the reading skills and interest of students at the Miftahul Ulum Yosorati Islamic Boarding School in Sumberbaru, Jember. This research is motivated by the importance of reading the yellow books as a basic competency that students must possess in understanding classical Islamic knowledge. However, in reality, some students still experience difficulties in reading the yellow books and have a relatively low interest in reading. Therefore, the use of the Prakom Book is seen as an alternative learning method that can help students understand the basic rules of reading the yellow books more easily and systematically. This study used a qualitative approach with field research. The research subjects consisted of the boarding school supervisor, the ustaz (teacher) teaching the Prakom Book, and the students participating in the learning. Data collection techniques were conducted through interviews, observation, and documentation. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation and technical triangulation. The research results show that the use of the Prakom Book positively contributes to improving the reading ability of Islamic boarding school students. Through systematic, step-by-step, and easy-to-understand material, students more easily master the basics of nahwu and sharaf, which form the foundation for reading Islamic boarding school books. Furthermore, the use of the Prakom Book also increases students' interest in reading, as indicated by increased active participation in learning, enthusiasm for studying Islamic boarding school books, and motivation to deepen Islamic knowledge. Supporting factors for the successful use of the Prakom Book include the competence of the ustaz (teacher), a conducive Islamic boarding school environment, and supportive learning facilities. Inhibiting factors include differences in students' basic abilities and limited learning time. Abstrak Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis penggunaan Kitab Prakom dalam meningkatkan kemampuan dan minat membaca kitab kuning santri di Pondok Pesantren Miftahul Ulum Yosorati Sumberbaru Jember. Penelitian ini dilatarbelakangi oleh pentingnya kemampuan membaca kitab kuning sebagai kompetensi dasar yang harus dimiliki santri dalam memahami khazanah keilmuan Islam klasik. Namun, pada kenyataannya masih terdapat santri yang mengalami kesulitan dalam membaca kitab kuning serta memiliki minat baca yang relatif rendah. Oleh karena itu, penggunaan Kitab Prakom dipandang sebagai salah satu alternatif pembelajaran yang dapat membantu santri memahami kaidah-kaidah dasar membaca kitab kuning secara lebih mudah dan sistematis. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan (field research). Subjek penelitian terdiri atas pengasuh pesantren, ustaz pengampu pembelajaran Kitab Prakom, dan santri yang mengikuti pembelajaran. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Keabsahan data diuji melalui triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa penggunaan Kitab Prakom memberikan kontribusi positif terhadap peningkatan kemampuan membaca kitab kuning santri. Melalui materi yang disusun secara sistematis, bertahap, dan mudah dipahami, santri lebih mudah menguasai dasar-dasar nahwu dan sharaf yang menjadi fondasi dalam membaca kitab kuning. Selain itu, penggunaan Kitab Prakom juga mampu meningkatkan minat membaca santri yang ditandai dengan meningkatnya keaktifan dalam pembelajaran, antusiasme dalam mengkaji kitab kuning, serta motivasi untuk memperdalam pengetahuan keislaman. Faktor pendukung keberhasilan penggunaan Kitab Prakom meliputi kompetensi ustaz, lingkungan pesantren yang kondusif, serta dukungan sarana pembelajaran. Adapun faktor penghambatnya meliputi perbedaan kemampuan dasar santri dan keterbatasan waktu pembelajaran